Small Sample Lung Biopsy Findings in Patients With Clinicoradiologic Suspicion of Pulmonary Venoocclusive Disease–Pulmonary Capillary Hemangiomatosis. Issue 4 (October 2016) - Bal, Shakti K.; Thangakunam, Balamugesh; Irodi, Aparna; Gupta, Mayank; Christopher, Devasahayam J.
Abstract : Pulmonary venoocclusive disease (PVOD) and pulmonary capillary hemangiomatosis (PCH) form a sinister subgroup of pulmonary arterial hypertension where the predominant pathology lies in the pulmonary veins and capillaries, thus making the use of pulmonary vasodilators potentially dangerous in these patients. Radiologically, the presence of centrilobular nodules, interlobular septal thickening, and significant mediastinal adenopathy are useful in identifying this subgroup from patients with pulmonary arterial hypertension. The combination of all three has a sensitivity of 66% and a specificity of 100% in identifying this subgroup. We present a case series of 3 patients who were radiologically suspected to have PVOD or PCH and in whom pathologic corroborative evidence suggestive of PVOD and PCH was found in small sample lung biopsy specimens: transbronchial lung biopsy (2 patients) and trucut biopsy of the postmortem lung (1 patient). Histopathology, in our patients, showed pulmonary arteriole smooth muscle proliferation and narrowing, capillary proliferation, intimal fibrosis of pulmonary veins and arteries, interstitial fibrosis, interstitial foreign body type of multinucleate giant cells, and aggregates of alveolar and interstitial hemosiderophages. In conclusion, histopathology of small lung biopsy samples can provide useful corroborative pathologic evidence in patients with clinicoradiologic suspicion of PVOD-PCH.